2018
DOI: 10.1093/ajcn/nqy037
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, magnesium, and whole-milk intakes and high-aggressive prostate cancer in the North Carolina–Louisiana Prostate Cancer Project (PCaP)

Abstract: Among both African American and European American men diagnosed with prostate cancer, a higher Ca:Mg and whole-milk intake were associated with higher odds of high-aggressive prostate cancer. This study was registered at www.clinicaltrials.gov as NCT03289130.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 36 publications
2
17
1
Order By: Relevance
“…At present, targeted inhibition of cancer cell signaling network is suggested to be an effective strategy for the inhibition of cancer cell proliferation and migration (Seydi, Salimi, Rasekh, Mohsenifar, & Pourahmad, 2018). Isoflavones as therapeutic agents for the treatment of cancer have gained much attention due to their low cytotoxic effects and ability to modulate multiple apoptosis pathways (Budryn, Grzelczyk, & Pérez-Sánchez, 2018;Kaushik, Shyam, Sharma, & Balapure, 2018;Malloy et al, 2018). Similarly, in this study, we found that glycitein inhibited gastric cancer cell line growth at different concentrations for 24 hr.…”
Section: Discussionsupporting
confidence: 64%
“…At present, targeted inhibition of cancer cell signaling network is suggested to be an effective strategy for the inhibition of cancer cell proliferation and migration (Seydi, Salimi, Rasekh, Mohsenifar, & Pourahmad, 2018). Isoflavones as therapeutic agents for the treatment of cancer have gained much attention due to their low cytotoxic effects and ability to modulate multiple apoptosis pathways (Budryn, Grzelczyk, & Pérez-Sánchez, 2018;Kaushik, Shyam, Sharma, & Balapure, 2018;Malloy et al, 2018). Similarly, in this study, we found that glycitein inhibited gastric cancer cell line growth at different concentrations for 24 hr.…”
Section: Discussionsupporting
confidence: 64%
“…A recent study confirmed that in comparison to men who consumed < 1 servings/day of whole milk, those who drank ≥ 3 servings/day had an increased hazard of PCa mortality [282]. In 996 African American and 1064 European American men diagnosed with PCa, a higher whole milk intake was associated with higher odds of high-aggressive PCa [283]. Pettersson et al [284] showed that men with the highest versus lowest intake of whole milk were at an increased risk of PCa progression.…”
Section: Prostate Cancermentioning
confidence: 89%
“…Branched-chain fatty acids in milk and dairy products markedly enhance AMACR expression in PCa cells in vitro [289]. In contrast to whole milk, total dairy and fermented milk products did not correlate with PCa risk [281][282][283][284][285]. Milk fat and calcium are obviously not the primary causative nutritional factors in whole milk for PCa initiation and progression, as milk fat is abundant in cheese and other fermented milk products.…”
Section: Prostate Cancermentioning
confidence: 99%
“…A meta-analysis of the relevant literature did not reveal any correlations between the consumption of milk with different fat content and the risk of breast cancer [83]. However, the risk of aggressive prostate cancer was 74% higher in men who consumed the largest quantities of whole milk relative to subjects who did not consume whole milk [84]. Despite the fact that high consumption of dairy products has been linked with the risk of prostate cancer, the accumulated evidence is ambiguous, mainly due to statistical inconsistency [85].…”
Section: Annals Of Agricultural and Environmental Medicinementioning
confidence: 94%
“…The concentration of IGF-1 is several-fold higher in the milk of cows simulated with bovine somatotropin (rbGh) which radically increases milk yield and was approved for use in the USA in 1994 [87]. High blood levels of IGF-1 increase the risk of prostate and breast cancer [84,88,89]. For this reason, the use of rbGh in dairy cattle has been banned in all EU member states, Canada, Australia, New Zealand and Japan.…”
Section: Annals Of Agricultural and Environmental Medicinementioning
confidence: 99%